The LEDs luminance distribution measurement quality dependency on image focusing - Czyżewski, Dariusz (Photonics Letters of Poland, 2020)
Luminance measurements are used in a vast range of lighting technology fields. The author’s research has proved that measuring the luminance distribution on light source surface is the most challenging part of this process. The research has been conducted for a commercially available digital luminance distribution meter, with the goal of analyzing the influence of image focus settings and exposure parameters on the measured luminance values. It has been concluded that the incorrect image focus and inadequately matched exposure parameters (distance from the workpiece) contribute to quantitative changes in the information on luminance distribution on the LED surface and affect the precision the maximum luminance determination. Full Text: PDF References C. Xu, H. Cheng, and Y. Feng, "Optical design of rectangular illumination with freeform lenses for the application of LED road lighting," Frontiers of Optoelectronics, 2017, CrossRef D. Czyzewski, "LED substitutes of conventional incandescent lamps," Przeglad Elektrotechniczny, vol. 88, no. 11A, pp. 123-127, 2012. DirectLink W. R. Ryckaert, K. A. G. Smet, I. A. A. Roelandts, M. Van Gils, and P. Hanselaer, "Linear LED tubes versus fluorescent lamps: An evaluation," Energy and Buildings, 2012, CrossRef X.-H. Lee, I. Moreno, and C.-C. Sun, "High-performance LED street lighting using microlens arrays," Optics Express, 2013, CrossRef D. Czyzewski, "The street lighting luminaires with LEDs," Przeglad Elektrotechniczny, vol. 86, pp. 276-279, 2009. DirectLink D. Mozyrska, M. Wyrwas, and I. Fryc, "The determination of the LEDs colorimetric parameters, in the range of their operating temperature," Przeglad Elektrotechniczny, vol. 93, no. 4a, pp. 232-234, 2012. DirectLink J. Kowalska and I. Fryc, "Colour rendition quality of typical fluorescent lamps determined by CIE colour fidelity index and colour rendering index," Przeglad Elektrotechniczny, vol. 95, no. 7, pp. 94--97, 2019, CrossRef J. Kowalska, "Analysis of parameters describing the quality of the color rendering of light sources according to the IES TM-30-15 and the CIE 013.3-1995," Przeglad Elektrotechniczny, vol. 93, no. 6, pp. 50--54, 2017, CrossRef K. Houser, M. Mossman, K. Smet, and L. Whitehead, "Tutorial: Color Rendering and Its Applications in Lighting," LEUKOS - Journal of Illuminating Engineering Society of North America, vol. 12, no. 1-2, pp. 7-26, 2016, CrossRef S. Słomiński, "Identifying problems with luminaire luminance measurements for discomfort glare analysis," Lighting Research and Technology, 2016, CrossRef D. Czyzewski, "Investigation of COB LED luminance distribution," 2016, CrossRef M. Jongewaard, "Guide to selecting the appropriate type of light source model," in Proc.SPIE, Aug. 2002, vol. 4775, CrossRef D. Czyzewski, "Selected problems of defining the luminous area of electroluminescent diodes," Przeglad Elektrotechniczny, vol. R. 84, nr 8, pp. 125-128, 2008. DirectLink C. D. Galatanu, "Improving the Luminance Measurement from Digital Images," in 2019 International Conference on Electromechanical and Energy Systems (SIELMEN), 2019, pp. 1-4. CrossRef I. Fryc and E. Czech, "Application of optical fibers and CCD array for measurement of luminance distribution," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 18-21, CrossRef I. Fryc and E. Czech, "Spectral correction of the measurement CCD array," Optical Engineering, 2002, CrossRef I. Fryc, "Angular characteristics of a silicon detector spectral sensitivity corrected by an absorption filter," in Proc. SPIE 4517, Lightmetry: Metrology, Spectroscopy, and Testing Techniques Using Light, 2001, pp. 42-45, CrossRef I. Fryc, "Accuracy of spectral correction of a CCD array for luminance distribution measurement," in Proc. SPIE 5064, Lightmetry 2002: Metrology and Testing Techniques Using Light, 2003, pp. 38-42, CrossRef M. Moeck and S. Anaokar, "Illuminance analysis from high dynamic range images," LEUKOS - Journal of Illuminating Engineering Society of North America, pp. 211-228, 2006, CrossRef D. Czyżewski, "Research on luminance distributions of chip-on-board light-emitting diodes," Crystals, 2019, CrossRef